Design and synthesis of coumarin–glyoxal hybrids for spermicidal and antimicrobial actions: a dual approach to contraception. Issue 80 (11th August 2016) - Gupta, Swati; Kushwaha, Bhavana; Srivastava, Akansha; Maikhuri, Jagdamba Prasad; Sankhwar, Satya N.; Gupta, Gopal; Dwivedi, Anil Kumar
Abstract : Today there is an urgent need for safe and effective dual-purpose contraceptive agents, which can simultaneously prevent unintended pregnancies and sexually transmitted infections (STI). Abstract : Today there is an urgent need for safe and effective dual-purpose contraceptive agents, which can simultaneously prevent unintended pregnancies and sexually transmitted infections (STI). There are several naturally occurring antimicrobial and antibiotic drugs (novobiocin, coumermycin and chlorobiocin) reported in the literature, which are based on 4-hydroxy coumarins as the active pharmacophore. Based on these interesting reports, we designed and synthesized a library of new 4-hydroxy coumarin derivatives and evaluated them for spermicidal activity. Among the tested compounds, two compounds (2a and2d ) displayed better activity (greater than 95% sperm immobilization at 0.5 mM concentration) than the positive control nonoxynol-9 (N-9 ). Furthermore, all the compounds were screened for antimicrobial activity against different strains of Trichomonas vaginalis and two compounds (2c and2h ) exhibited potent activity as compared to the reference drug metronidazole. The cytotoxicity assay showed that most of these compounds were safer than the N-9 against the human cervical HeLa cell line and normal vaginal flora Lactobacillus jensenii strains. The studies have demonstrated that compound (2a ) is a potential lead to develop a dually active vaginal contraceptive.